Haplotype Diversity of COI Gene of Hylarana chalconota Species Found at State University of Malang - Wulandari, Dian Ratri; Ibrohim, Ibrohim; Listyorini, Dwi (Journal of Tropical Life Science, 2014)
Hylarana chalconota is a cryptic species of frog endemic to Java Island . This species is small with long legs, and brown skin. The Snout-Vent Length (SVL) ranges between 30-40 mm for male and 45-65 mm for female. Reports the existence of this species in State University of Malang, which was not found in 1995. To reveal the haplotype diversity of COI gene in this species, we analyzed Cytochrome-c oxidase subunit-1 (COI) sequences of both samples. The both samples had 604 bp and 574 bp fragment length, respectively. These fragments showed polymorphism; with mutation position in sites 104, 105, and 124. Based on this result, we suggest that the two samples share a different haplotypes, proposed as UM1 and UM2